Cleaner personality and client identity have joint consequences on cleaning interaction dynamics. (29th January 2019) - Dunkley, Katie; Ioannou, Christos C; Whittey, Kathryn E; Cable, Jo; Perkins, Sarah E
Abstract: Mutualistic interactions involve 2 species beneficially cooperating, but it is not clear how these interactions are maintained. In many mutualisms, one species interacts with multiple species, and since partners differ in terms of the commodities they trade, partner identity will directly influence the decisions and behaviors of interacting individuals. Here, we investigated the consequences of within and between-species diversity on a model cleaner–client interaction in a natural environment, by quantifying the behavior of both partners. We found that the predominant Caribbean cleaner fish, the sharknose goby ( Elacatinus evelynae ), shows personality variation as we documented repeatable individual differences in activity, boldness, and exploratory behaviors. Personality variation was associated with cleaner–client interactions: cleaner boldness and activity were significantly related to posing by clients and cleaning, respectively. Cleaner personality variation was also associated with the functional identity (sociality, mobility, body size, and trophic level) of clients posing and being cleaned. We thus demonstrate that partner identity can have consequences on mutualistic outcomes which will contribute to the context-dependency and highly heterogeneous patterns we observe at a population level. We also suggest that within- and between-species differences have consequences on partner choice, a feature that has been previously thought to be absent from these cleaner–client interactions. Abstract : Cleaner fish personality links with client identity to determine who interacts with whom and how. Our field study demonstrates that both client and cleaner identities contribute jointly to the variable patterns we observe for mutualisms. We challenge the existing paradigm that Caribbean cleaning gobies represent a "simple" system for studying cleaner–client interactions.